Ventrally exophytic pontine mass in a patient with dysarthria, dysphagia and diplopia: Answer. (April 2021) - Ovenden, Christopher; O'Donohoe, Thomas; Santoreneos, Stephen
Highlights: Intra-axial pontine lesions can present with a mixture of long tract signs and cranial nerve dysfunction. In rare cases high grade glioma occurs in this region. These lesions can be ventrally exophytic and encase the basilar artery.